Characterization and Anti-Bacterial Activity Testing of the Nano Hydroxyapatite-Clove (Eugenia Caryophyllus) Against Streptococcus Mutans Bacteria - Akbar, Achmad Fitriadi; Cahyaningrum, Sari Edi (Universitas Negeri Semarang, 2022)
Hydroxyapatite is one of the materials as a source of calcium and phosphate in the tooth remineralization process. Several studies have shown that hydroxyapatite produces strong antibacterial activity against caries-causing bacteria. Dental caries are one of the tooth scrapings suffered by many people. Dental caries are caused by Streptococcus mutans. In addition to hydroxyapatite, essential oil derived from cloves also has a good antimicrobial function. The eugenol content in cloves can kill bacteria that are resistant to antibiotics. This study aims to determine the results of the physicochemical characterization and antibacterial test of Streptococcus mutans in the clove-hydroxyapatite nanoformulation. This study used a nano-hydroxyapatite-clove test material with various compositions of 0.5 mL, 1 mL, 2 mL, 3 mL, and 4 mL of clove oil, 1% hydroxyapatite, Tween, and propylene glycol. The results of FT-IR characterization showed OH, C-H, C-O, C=O, PO43-, and CO32- functional groups. In PSA testing, the smallest size is indicated by the variation in the composition of 1ml clove oil, which is 16.07nm. The measurement of the antibacterial activity test showed that the hydroxyapatite-clove nanoformulation was able to inhibit the growth of Streptococcus mutans bacteria, with normally distributed data (p=0,05) and produce a significant probability,000 (p<0,05).